Achieving scarless renal surgery: is it feasible?. (December 2014) - Tay, Li June; Hadjipavlou, Marios; Khan, Shahid; Rane, Abhay
Renewed interest in 'scarless' surgery has been generated by the advent of natural orifice transluminal endoscopic surgery and laparoendoscopic single-site surgery (LESS). Both techniques aim at minimizing surgical scarring and morbidity, thereby improving recovery. We appraise the literature and examine the future perspectives of these techniques in renal surgery. Successful applications in renal extirpative surgery with natural orifice transluminal endoscopic surgery have been reported, but it still remains a technique in evolution. LESS is gradually being embraced and contemporary procedures such as nephrectomy and pyeloplasty are increasingly being performed. Evidence endorsing the benefits of LESS still remains limited. Innovations in technology, instrumentation and the incorporation of robotic systems has opened up fascinating avenues and the dream of truly 'scarless' surgery seems achievable.